2014
DOI: 10.1152/ajplung.00167.2013
|View full text |Cite
|
Sign up to set email alerts
|

Long-term effects of carbon containing engineered nanomaterials and asbestos in the lung: one year postexposure comparisons

Abstract: The hallmark geometric feature of single-walled carbon nanotubes (SWCNT) and carbon nanofibers (CNF), high length to width ratio, makes them similar to a hazardous agent, asbestos. Very limited data are available concerning long-term effects of pulmonary exposure to SWCNT or CNF. Here, we compared inflammatory, fibrogenic, and genotoxic effects of CNF, SWCNT, or asbestos in mice 1 yr after pharyngeal aspiration. In addition, we compared pulmonary responses to SWCNT by bolus dosing through pharyngeal aspiration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
101
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 108 publications
(111 citation statements)
references
References 80 publications
5
101
0
Order By: Relevance
“…We have also reported that a single intratracheal administration of SWCNTs with an average length of 0.69 lm did not induce lung tumors at 108 weeks after instillation (Fujita et al, 2015a). However, a substantial number of SWCNTs accompanied with chronic inflammation and fibrotic changes were observed in the lungs at 1-year post exposure to SWCNTs (Fujita et al, 2015a;Shvedova et al, 2014). We observed a continuous elevation in the levels of lactose dehydrogenase, total protein levels, and some cytokines in bronchoalveolar lavage fluid when SWCNTs were administrated by intratracheal instillation (Ema et al, 2017;Fujita et al, 2015aFujita et al, , 2015bFujita et al, , 2016.…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…We have also reported that a single intratracheal administration of SWCNTs with an average length of 0.69 lm did not induce lung tumors at 108 weeks after instillation (Fujita et al, 2015a). However, a substantial number of SWCNTs accompanied with chronic inflammation and fibrotic changes were observed in the lungs at 1-year post exposure to SWCNTs (Fujita et al, 2015a;Shvedova et al, 2014). We observed a continuous elevation in the levels of lactose dehydrogenase, total protein levels, and some cytokines in bronchoalveolar lavage fluid when SWCNTs were administrated by intratracheal instillation (Ema et al, 2017;Fujita et al, 2015aFujita et al, , 2015bFujita et al, , 2016.…”
Section: Discussionmentioning
confidence: 80%
“…Only a few studies on the longterm effects of airway exposure to SWCNTs have been published. Data from a 1-year observational study in mice on purified HiPco SWCNTs (1-3 lm in length) revealed no increase in the incidence of lung tumors after inhalation at 5 mg/m 3 (5 h/d for 4d) or a single pharyngeal aspiration at 40 lg/mouse (Shvedova et al, 2014). In rats, no pulmonary tumors were detected 754 d after a single intratracheal instillation of SWCNTs at 0.2 or 0.4 mg/rat (0.69 lm of average length) (Fujita et al, 2015a).…”
Section: Test Substance Findingsmentioning
confidence: 96%
See 1 more Smart Citation
“…In a one-year observational study on purified HiPco SWCNTs (0.1-1 μm in length) in mice, no increased incidence of lung tumor was reported after administration of the SWCNTs by inhalation or pharyngeal aspiration (Shvedova et al, 2014b). Furthermore, in a study conducted in rats, no pulmonary tumor was detected 754 days after intratracheal instillation of SWCNTs (average length, 0.69 μm) (Fujita et al, 2015b).…”
Section: Discussionmentioning
confidence: 95%
“…Furthermore, in a study conducted in rats, no pulmonary tumor was detected 754 days after intratracheal instillation of SWCNTs (average length, 0.69 μm) (Fujita et al, 2015b). However, a substantial number of SWCNTs as well as inflammation and fibrotic changes were observed in the lungs of the rats at 1-year post exposure to the SWCNTs (Shvedova et al, 2014b;Fujita et al, 2015b). In the present study, we showed that S-SWCNTs induced persistent pulmonary inflammation and L-SWCNTs caused increased levels of total protein in BALF during the later phase of the 6-month observational period.…”
Section: Discussionmentioning
confidence: 97%